Immunological design of commensal communities to treat intestinal infection and inflammation - Brown,RL; Larkinson,MLY; Clarke,TB (PLoS Pathogens, 2021)
The immunological impact of individual commensal species within the microbiota is poorly understood limiting the use of commensals to treat disease. Here, we systematically profile the immunological fingerprint of commensals from the major phyla in the human intestine (Actinobacteria, Bacteroidetes, Firmicutes and Proteobacteria) to reveal taxonomic patterns in immune activation and use this information to rationally design commensal communities to enhance antibacterial defenses and combat intestinal inflammation. We reveal that Bacteroidetes and Firmicutes have distinct effects on intestinal immunity by differentially inducing primary and secondary response genes. Within these phyla, the immunostimulatory capacity of commensals from the Bacteroidia class (Bacteroidetes phyla) reflects their robustness of TLR4 activation and Bacteroidia communities rely solely on this receptor for their effects on intestinal immunity. By contrast, within the Clostridia class (Firmicutes phyla) it reflects the degree of TLR2 and TLR4 activation, and communities of Clostridia signal via both of these receptors to exert their effects on intestinal immunity. By analyzing the receptors, intracellular signaling components and transcription factors that are engaged by different commensal species, we identify canonical NF-κB signaling as a critical rheostat which grades the degree of immune stimulation commensals elicit. Guided by this immunological analysis, we constructed a cross-phylum consortium of commensals (Bacteroides uniformis, Bacteroides ovatus, Peptostreptococcus anaerobius and Clostridium histolyticum) which enhances innate TLR, IL6 and macrophages-dependent defenses against intestinal colonization by vancomycin resistant Enterococci, and fortifies mucosal barrier function during pathological intestinal inflammation through the same pathway. Critically, the setpoint of intestinal immunity established by this consortium is calibrated by canonical NF-κB signaling. Thu